Efforts to Increase Electricity Sales at Pln Ulp Belawan Customer Service Zone Using AHP-ANP Method Implementation - Robby Sepriadi; Mohammad Isa Irawan (Journal of Research in Social Science and Humanities, 2025)
Abstract Electricity sales represent a crucial aspect of the business operations of the Perusahaan Listrik Negara (PLN). PLN is required to continuously improve its electricity sales strategies and enhance its services to meet the growing demands of its customers. PLN’s Customer Service Unit (ULP) Belawan is located in the northern part of Medan City, North Sumatra Province. PLN ULP Belawan serves a total of 75,931 customers with a total installed capacity of 220.28 MVA. In 2023, electricity sales reached 484.86 GWh, which is 105.63% of the target. The sales target for 2024 has been set at 524.46 GWh. This thesis aims to present the results of customer zoning prioritization that can be used to improve service delivery more effectively within PLN ULP Belawan. Through the weighting process using Analytic Hierarchy Process (AHP) and Analytic Network Process (ANP), as multi-criteria decision-making methods, were to optimize criteria and contribute to enhancing electricity sales performance. Each customer zone was evaluated based on several criteria, including system reliability, electricity usage regulation (P2TL), improvement of disturbance and complaint services, replacement of electricity meters, enforcement of the 720-hour usage regulation, connection criteria, cash-in performance, and accurate meter reading. The research successfully identified customer zones based on priority criteria. For the criterion of Electricity Usage Regulation (P2TL), the total energy recorded was 341,841 kWh across 173 kWh meters. Of this total, Zone 12 contributed the most with 277,019 kWh, followed by Zone 14 with 43,098 kWh, and Zone 6 with 20,914 kWh. In the Accurate Meter Reading criterion, the total energy achieved was 157,311 kWh from 815 kWh meters. Zone 14 contributed the highest amount at 67,564 kWh, followed by Zone 12 with 48,580 kWh, and Zone 6 with 41,167 kWh. Meanwhile, for the criterion of Electricity Meter Replacement, the total energy gained was 65,559 kWh from 505 kWh meters, with the largest contribution coming from Zone 6 (26,910 kWh), followed by Zone 12 (26,688 kWh), and Zone 14 (11,961 kWh).